2020
DOI: 10.3389/fpsyt.2020.00387
|View full text |Cite
|
Sign up to set email alerts
|

Not the Root of the Problem—Hair Cortisol and Cortisone Do Not Mediate the Effect of Child Maltreatment on Body Mass Index

Abstract: Background: Experiencing maltreatment during childhood exerts substantial stress on the child and increases the risk for overweight and obesity later in life. The current study tests whether hair cortisol-a measure of chronic stress-and its metabolite cortisone mediate the relation between abuse and neglect on the one hand, and body mass index (BMI) on the other. Method: The sample consisted of 249 participants aged 8 to 87 years (M = 36.13, SD = 19.33). We collected data on child abuse and neglect using quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 110 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…The literature search identified 1017 unique citation titles of which a total of 120 studies 5,13,14,16,19,30,33–146 comprising 146 separate cohorts were included (Figure 1). This corresponds to a total of 34,342 included participants of which 15,698 (46%) were sampled from general population‐based studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 1017 unique citation titles of which a total of 120 studies 5,13,14,16,19,30,33–146 comprising 146 separate cohorts were included (Figure 1). This corresponds to a total of 34,342 included participants of which 15,698 (46%) were sampled from general population‐based studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a large-volume study conducted on US population showed that risk factor for developing Parkinson's disease increases with decreasing darkness of hair color [ 15 ]. Moreover, a recent report revealed that there is no direct effect of hair cortisol and hair cortisone on BMI [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants with offspring were invited to visit the laboratory twice—once with their family of origin (parents and siblings) and once with their partner and offspring. A laboratory visit took approximately 7 hours and involved questionnaires, computer tasks, family interaction tasks, and collection of saliva and hair samples (e.g., Pittner et al, 2020). Informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%